Time-resolved cryo-EM visualizes ribosomal translocation with EF-G and GTP - Carbone, Christine E; Loveland, Anna B; Gamper, Howard B; Hou, Ya-Ming; Demo, Gabriel; Korostelev, Andrei A (Nature communications, 2021)
During translation, a conserved GTPase elongation factor-EF-G in bacteria or eEF2 in eukaryotes-translocates tRNA and mRNA through the ribosome. EF-G has been proposed to act as a flexible motor that propels tRNA and mRNA movement, as a rigid pawl that biases unidirectional translocation resulting from ribosome rearrangements, or by various combinations of motor- and pawl-like mechanisms. Using time-resolved cryo-EM, we visualized GTP-catalyzed translocation without inhibitors, capturing elusive structures of ribosome•EF-G intermediates at near-atomic resolution. Prior to translocation, EF-G binds near peptidyl-tRNA, while the rotated 30S subunit stabilizes the EF-G GTPase center. Reverse 30S rotation releases Pi and translocates peptidyl-tRNA and EF-G by ~20 Å. An additional 4-Å translocation initiates EF-G dissociation from a transient ribosome state with highly swiveled 30S head. The structures visualize how nearly rigid EF-G rectifies inherent and spontaneous ribosomal dynamics into tRNA-mRNA translocation, whereas GTP hydrolysis and Pi release drive EF-G dissociation.
Keywords: messenger RNA; RNA transferová; Cryoelectron Microscopy; RNA, Transfer, Amino Acyl; Protein Binding; Ribosomes; elongační faktor G; ribozomy; Guanosine Triphosphate; proteosyntéza; RNA, Transfer; Protein Biosynthesis; Escherichia coli; Peptide Elongation Factor G; aminoacyl-tRNA; elektronová kryomikroskopie; RNA, Messenger; vazba proteinů; Ribosome Subunits, Small, Bacterial; Phosphates; fosfáty; guanosintrifosfát; malé podjednotky ribozomu bakteriální